LINEAMENT ANALYSIS OF SULAIMANI MASTER PLAN AREA, KURDISTAN REGION, IRAQ - Bety, Azhar; Al-Qayim, Basim; Al-Daghistani, Hikmat (Sulaimani Journal for Pure and Applied Sciences, 2016)
Modern technologies in the field of remote sensing and geographic information systems are used to process the available data to produce maps for lineaments types, distribution and lineaments density within the area of the master plan of Sulaimani city. Three scenes image of Spot satellite with panchromatic mode from date 12-2008 with ground resolution of 5 meter were selected for this analysis. Statically analysis of lineaments was taken in order to classify them according to their length and direction, also the general trend was found, then classification was done according to their density. For all analysis maps were produced by using Arc GIS program. The results show four classes of lineaments according to their length short, linear, long and regional lineaments within NE-SW as a general direction within the study area. The distribution or the density of lineaments found to be 9.2 liners per km2 where the numbers of lineaments is 4365, with total length up to 3801 km. Most parts of the area fall between low density, density and high density classes where very low and very high density classes cover small areas relatively according to the density of the lineaments.
Keywords: Remote SensingGISLineamentsClassificationAnd Density